Mechanical And Tribological Properties Of Ultra High Molecular Weight Polyethylene With Zinc Oxide Antibacterial Agent For Joint Implant - Chan, Boon Peng (2014)
Total joint replacement (TJR) is a highly successful treatment for end-stage joint disease like osteoarthritis. A prominent number of TJR devices used in orthopaedic involve articulation between a metallic alloy and ultra-high molecular weight polyethylene (UHMWPE). Although this polymer has excellent properties, suitable for TJR bearing materials, the wear particulate produced due to relative motion between components still remains an issue yet to be resolved. This study presents approaches to improve the wear performance of UHMWPE in implant applications by various types of fillers reinforcement. The UHMWPE composites were fabricated by compression moulding with different filler-matrix ratios. These composites were characterized and compared in terms of their mechanical and tribological properties. The filler which delivered the best performances were selected as the filler in the UHMWPE hybrid composites. The tribological properties was investigated using pin-on-disc tester under different loads and sliding speeds. The worn surfaces and transfer films produce after wear test were studied under scanning electron microscopy (SEM). This research consists of four parts. The first part was to investigate the effect of surface treatment of ZnO on the mechanical, tribological and antibacterial properties. Two variants of untreated ZnO-reinforced UHMWPE (U-ZPE) and treated ZnO-reinforced UHMWPE (T-ZPE) with aminoproply-triethoxysilane (APTES) were used to compare the improvement of properties. The antibacterial assessments of the composites were tested against two common human body bacteria i.e. Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus).